IMPLEMENTASI ALIH KODE GURU DALAM PEMBELAJARAN BAHASA INDONESIA DI SEKOLAH DASAR: ANALISIS BENTUK DAN FUNGSI DI KELAS III SD NEGERI 5 MANUKAYA - Dewa Ayu Widiasri; Ni Wayan Widi Astuti (LP3M Universitas PGRI Mahadewa Indonesia, 2026)
This study aims to describe the classification of code-switching forms and analyze the function of their use in Indonesian language learning in third-grade students at SD Negeri 5 Manukaya, Tampaksiring. This study used a qualitative approach with descriptive field research. The subjects were third-grade teachers as the primary informants and students as supporting informants. Data were collected through observation, interviews, and documentation techniques, then analyzed using the Miles and Huberman interactive analysis model, which includes data reduction, data presentation, and conclusion drawing. The results indicate that the dominant form of code-switching used by teachers is internal code-switching, namely switching between Indonesian and a regional language (Balinese). Code-switching occurs at various stages of learning, particularly during the core stages of material delivery. The use of code-switching is influenced by several factors, including internal factors such as language habits and teacher self-confidence, and external factors such as students' language backgrounds and social environments where regional languages ​​are more prevalent. Furthermore, code-switching serves an important function in learning: clarifying material, improving student understanding, and creating a more communicative and interactive learning environment. Thus, the proportional use of code-switching can support the effectiveness of Indonesian language learning in elementary schools.